Glyoxalase activity in human erythrocytes and mouse lymphoma, liver and brain probed with hyperpolarized 13C-methylglyoxal. (December 2018) - Shishmarev, Dmitry; Kuchel, Philip; Pagès, Guilhem; Wright, Alan; Hesketh, Richard; Kreis, Felix; Brindle, Kevin
Abstract Methylglyoxal is a faulty metabolite. It is a ubiquitous by-product of glucose and amino acid metabolism that spontaneously reacts with proximal amino groups in proteins and nucleic acids, leading to impairment of their function. The glyoxalase pathway evolved early in phylogeny to bring about rapid catabolism of methylglyoxal, and an understanding of the role of methylglyoxal and the glyoxalases in many diseases is beginning to emerge. Metabolic processing of methylglyoxal is very rapid in vivo and thus notoriously difficult to detect and quantify. Here we show that13 C nuclei in labeled methylglyoxal can be hyperpolarized using dynamic nuclear polarization, providing13 C nuclear magnetic resonance signal enhancements in the solution state close to 5, 000-fold. We demonstrate the applications of this probe of metabolism for kinetic characterization of the glyoxalase system in isolated cells as well as mouse brain, liver and lymphoma in vivo. Shishmarev et al. use rapid dissolution dynamic nuclear polarization to monitor glyoxalase activity in a non-invasive manner using nuclear magnetic resonance spectroscopy. They apply their method to monitor and quantify metabolism of methylglyoxal in human red blood cells and mouse tissues.